Controlled Drug Release: Magnesium Particles Coated with Mesoporous Nanoshells as Sustainable Therapeutic‐Hydrogen Suppliers to Scavenge Continuously Generated Hydroxyl Radicals in Long Term (Part. Part. Syst. Charact. 2/2019). (21st February 2019) - Kong, Lei; Chen, Chuanrui; Mou, Fangzhi; Feng, Yizheng; You, Ming; Yin, Yixia; Guan, Jianguo
Abstract : As demonstrated by Lei Kong, Fangzhi Mou, Jianguo Guan and co‐workers in article number1800424, magnesium microparticles coated with mesoporous SiO2 nanoshells show high‐efficient generation of vast quantities of therapeutic hydrogen in physiological condition with a rate controlled by the nanoshell thickness, and thus can eliminate excessive hydroxyl radicals in vivo over a long period.